Presence of angiotensin converting enzyme (ACE) interactive factors in ovaries of the grey fleshfly Neobellieria bullata. - Vandingenen, A; Hens, K; Macours, N; Schoofs, L; De Loof, A; Huybrechts, R (2002)
Angiotensin converting enzyme (ACE) activity, defined as a captopril-inhibitable dipeptidyl carboxypeptidase activity towards 3H-hippurylglycylglycine, was demonstrated in haemolymph, testes and ovaries of the grey fleshfly Neobellieria bullata, hereby suggesting a physiological role for ACE in these particular tissues. While the ACE activity in haemolymph and testes reached relatively high levels, only minute ACE activity could be detected in ovaries throughout the entire vitellogenic cycle. Ovarian extracts of Neobellieria bullata do contain, however, in addition to Neb-TMOF, the Neobellieria bullata trypsin modulating oostatic factor which is an in vitro and a putative in vivo substrate of ACE in circulation, several other heat-stable molecules which individually function either as an ACE substrate or ACE inhibitor. Presumably these ACE interactive factors mask ACE activity in the fly ovaries, as measured by a classic substrate-binding assay. Purification and characterisation of these ACE substrates/inhibitors is in progress and is likely to facilitate the elucidation of the enigmatic physiological relevance of ACE in insects.